Gaseous and particulate water-soluble organic and inorganic nitrogen in rural air in southern Scotland - Gonzalez Benitez, Juan M; Cape, J Neil; Heal, Mathew R (Elsevier, 2010)
Simultaneous daily measurements of water-soluble organic nitrogen (WSON), ammonium and nitrate were made between July and November 2008 at a rural location in south-east Scotland, using a ‘Cofer’ nebulizing sampler for the gas phase and collection on an open-face PTFE membrane for the particle phase. Average concentrations of NH3 were 82 ± 17 nmol N m-3 (error is s.d. of triplicate samples), while oxidised N concentrations in the gas phase (from trapping NO2 and HNO3) were smaller, at 2.6 ± 2.2 nmol N m-3, and gas-phase WSON concentrations were 18 ± 11 nmol N m-3. The estimated collection efficiency of the nebulizing samplers for the gas-phase was 88 (±8) % for NH3, 37 (±16) % for NO2 and 57 (±7) % for WSON; reported average concentrations have not been corrected for sampling efficiency. Concentrations in the particle phase were smaller, except for nitrate, at 21 ± 9, 10 ± 6 and 8 ± 9 nmol N m-3, respectively. The absence of correlation in either phase between WSON and either (NH3 + NH4+) or NO3- concentrations suggests atmospheric WSON has diverse sources. During wet days, concentrations of gas and particle-phase inorganic N were lower than on dry days, whereas the converse was true for WSON. These data represent the first reports of simultaneous measurements of gas and particle phase water-soluble nitrogen compounds in rural air on a daily basis, and show that WSON occurs in both phases, contributing 20-25% of the total water-soluble nitrogen in air, in good agreement with earlier data on the contribution of WSON to total dissolved N in rainfall in the UK.
Keywords: Cofer sampler; water-soluble organic nitrogen; DON; reactive nitrogen